Automated Reporting System Pilot Project in Los Angeles, 1990 - Doan, David ([Verlag nicht ermittelbar], 1993)
The purpose of this pilot project was to determine if preliminary investigation report (PIR) data filed by patrol officers could be collected via laptop computers to allow the direct input of the data into the Los Angeles Police Department Crime and Arrest Database without adversely affecting the personnel taking or using the reports. This data collection addresses the following questions: (1) Did officers and supervisors prefer the automated reporting system (ARS) or the handwritten version of the PIR? (2) Did the ARS affect the job satisfaction or morale of officers and supervisors? (3) Did the ARS reduce the amount of time that patrol officers, supervisors, and clerks spent on paperwork? (4) Did the ARS affect the accuracy of information contained in the PIRs? (5) Did detectives and prosecuting attorneys find the ARS a more reliable source than handwritten PIRs? Officers and supervisors in two divisions of the Los Angeles Police Department, Wilshire and Hollywood, participated as control and experimental groups. The control group continued using handwritten ("existing") PIRs while the experimental group used the automated PIRs (ARS). The General Information Questionnaire collected information on each officer's rank, assignment, watch, gender, age, years with the Los Angeles Police Department, education, job morale, job demands, self-esteem, computer anxiety, and relationship with supervisor and other officers. The Job Performance Rating Form gathered data on work efforts, depth of job knowledge, work quality, oral and written skills, and capacity to learn. The Time Study Sheets collected data on investigation time, writing and editing time, travel time, approval and correction time, review time, errors by type, and data input time for both the handwritten and automated forms. The Evaluation of the Existing Form and the Evaluation of the Automated Form both queried respondents on ease of use, system satisfaction, and productivity loss. The ARS Use Questionnaire asked about ease of use, typing skills, computer skills, comfort with the system, satisfaction with training, and preference for the system. The Hollywood Detective Division ARS Use Questionnaire surveyed detectives on the system's ease of use, task improvement, support for continued use, and preference for the system. The PIR Content Evaluation Form collected data on quality of officers' observations, organization and writing skills, physical evidence, statements of victims, witnesses, and suspects, and offense classification. The Caplan Role Conflict and Role Ambiguity subscales were used in the design of the questionnaires.